2019
DOI: 10.3390/en12203980
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Photoperiod and Quality Assessment of Basil Plants Grown in a Small-Scale Indoor Cultivation System for Reduction of Energy Demand

Abstract: Vertical farming is a novel type of food production in indoor environments with artificial lighting and controlled cultivation conditions. In this context, sustainability in small-scale indoor cultivation systems is crucial. Sustainability can be achieved by optimizing all the cultivation factors involved in the production process. The effects of different photoperiod conditions under different timing during plant development—from sowing to germination and maturity—have been studied in a small-scale indoor cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The daily light integral (DLI) is the most important for plants, and previous studies have shown that the optimal DLI for basil is about 12.9 mol m −2 d −1 ; this would be 224 µmol m −2 s −1 at 16 h photoperiod [26]. However, there have been reports in which the photoperiod did not significantly affect the growth and physiological properties of basil, but it is recognized that it is necessary to analyze the effects of the light intensity and photoperiod [27]. In addition, Kiferle et al [28] emphasize that basils need a low concentration of nitrogen for optimal plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…The daily light integral (DLI) is the most important for plants, and previous studies have shown that the optimal DLI for basil is about 12.9 mol m −2 d −1 ; this would be 224 µmol m −2 s −1 at 16 h photoperiod [26]. However, there have been reports in which the photoperiod did not significantly affect the growth and physiological properties of basil, but it is recognized that it is necessary to analyze the effects of the light intensity and photoperiod [27]. In addition, Kiferle et al [28] emphasize that basils need a low concentration of nitrogen for optimal plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study describes how waste heat from fossil fuel power plants is imported to nearby PFALs, thereby reducing CO 2 emissions by 1204 tons per year [22]. Some PFALs avoid electricity peaks during the daytime by switching on lights only at night to utilize surplus electricity [20,23]. The area around industrial factories and mining operations is particularly worrisome with pollution rising significantly to 36.3% [24].…”
Section: Indoor Urban Vertical Farmingmentioning
confidence: 99%
“…As a result, indoor farms typically price product toward the high end and along the lines of pricing for organics, 2 which limits market penetration. The 2 major factors contributing to the high costs of indoor and vertical farm operations are energy 10,23,24 and labor, which account for nearly 3 quarters of the total. 2,24 Despite these challenges, venture capital continues to pour money into indoor farming and agtech in the hopes of driving cost down and maintaining growth.…”
Section: Benefits and Challenges Of Indoor Vertical Farmsmentioning
confidence: 99%
“…Research on indoor farming and vertical farming has been ongoing for several years and represents multiple topics and streams. A map produced by VOSviewer 26 of the research landscape of ideas based on the co-occurrence of keywords (eg, "vertical farming"; "indoor farming") appearing in Scopus is Research on indoor farming includes farm production capabilities, 12 profitability and economics, 18,27 pest and disease management, 28 building information modeling, 29 energy management, 23,30 sustainability, urban planning and food security, 3,9,14-16 plant science, 13 and smart farming. 11 An excellent source of knowledge on indoor farming and plant factories can be found in Kozai et al 8,9 Topics include the impact of indoor farms on urban areas, global case studies, energy and resource use, operating efficiencies, plant science, systems design, growing methods and materials, indoor production processes, measurement, automation, sustainability of indoor farms, and next-generation designs.…”
Section: Research On Indoor Farmingmentioning
confidence: 99%